Density of mast cells in lesions of actinic cheilitis. - Rachel Reinaldo Arnaud (Editorial Ciencias Médicas, 2014)
Objective: Analyze the density of mast cells in Actinic cheilitis according to the histological characteristics of the lesion compared with the normal mucosa. Material and Methods: Descriptive study where the sample consisted of two groups, the first with 33 specimens of cases of actinic cheilitis diagnosed clinically, and the second consists of 9 specimens of normal oral mucosa, registered in the Service of Head and Neck Hospital Dr. Napoleon Laureano, João Pessoa, PB. The paraffin blocks of the sample were cut and stained with hematoxylin and eosin to assess the degree of dysplasia and inflammatory infiltrate, and toluidine blue to quantify mast cells. The count of mast cells was performed with the aid of a square grid in the case of field 8. The final reading was expressed with an average value of mast cells by case / μm². Data were analyzed by SPSS (Statistical Package for Social Sciences) version 15.0. Results: In 57.6% of cases there was some degree of dysplasia, and 39.4% mild, 15.2% moderate and 3% severe. 21.2% had squamous cell carcinoma. The presence of inflammatory infiltrate and solar elastosis was observed in 84.9% and 81.8%, respectively. Mast cells were identified in 87.8% of the sample. The density of mast cells in cases of Actinic Cheilitis was 17.4 ± 10.4 cells / μm² and 1.78 ± 1.64 normal tissue cells / μm² (p <0.001). There was a statistically significant correlation between mast cell density with the processes of dysplasia (p = 0.004) and inflammatory cell infiltration (p = 0.000). Conclusion: The increase in mast cell density in actinic cheilitis lesions and its correlation with the processes of inflammation and dysplasia suggest involvement of these cells in disease progression for Squamous Cell Carcinoma lip.